Republic of Madagascar : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Madagascar's Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Madagascar's performance under the program in 2004 has been broadly satisfactory, particularly in light of the difficult economic environment that prevailed during the first half of the year. All quantitative performance criteria at end-September and the structural performance criterion at end-December have been met. Further steps are needed to strengthen monetary policy implementation. Implementation of public enterprise reform, which has been uneven, also needs to be accelerated.